What is new in diagnostics and therapy in dermatology? - Szepietowski, Jacek; Reich, Adam (Przewodnik Lekarza/Guide for GPs, 2007)
Rapid progress of the diagnostic procedures and therapy of skin diseases has been observed during the last few years. Nowadays, the exact diagnosis of many skin diseases cannot be done without use of the newest developments of molecular biology, and the recently discovered drugs have significantly improved the spectrum and efficacy of the treatment of dermatoses. In the current paper the authors have tried to present recent developments of diagnostics and therapy of the most common skin diseases, including tinea pedis, acne vulgaris, seborrheic dermatitis, atopic dermatitis, eczema and psoriasis.